Role of the Glyoxalase System in Breast Cancer and Gynecological Cancer-Implications for Therapeutic Intervention: a Review - Jingyuan Wang; Xiao Yang; Zhiqi Wang; Jianliu Wang (Frontiers in Oncology, 2022)
Methyglyoxal (MGO), an essential endogenous dicarbonyl metabolite, can lead to multiple physiological problems including hyperglycemia, kidney diseases, malignant tumors, beyond its normal concentration range. The glyoxalase system, making MGO maintained at a low level, links glycation to carcinogenesis, growth, metastasis, and cancer chemotherapy. The glyoxalase system comprises glyoxalase 1 (Glo1) and glyoxalase 2 (Glo2), which is often overexpressed in various tumor tissues. However, very little is known about the glyoxalase system in breast cancer and gynecological cancer. In this review, we introduce the role of the glyoxalase system in breast cancer, endometrial cancer, ovarian cancer and cervical cancer, and highlight the potential of the glyoxalase system to be both as a marker for diagnosis and a novel target for antitumor therapy. However, the intrinsic molecular biology and mechanisms of the glyoxalase system in breast cancer and gynecological cancer need further exploration.